Secondary Leukemia in a non-Hodgkin's Lymphoma Patient Presenting as Myeloid Sarcoma of the Breast - Pitini, Vincenzo; Arrigo, Carmela; Sauta, Maria Grazia; Altavilla, Giuseppe (Case Reports in Hematology, 2011)
As defined by the World Health Organization classification of tumors of hematopoietic and lymphoid tissue, myeloid sarcoma (MS) is a tumor mass of myeloblasts or immature myeloid cells that can arise before, concurrent with, or following acute myeloid leukaemia. We describe a case of secondary leukemia presenting itself as MS of the breast in a patient previously treated for a non-Hodgkin's Lymphoma.